A feature-based Machining Using Function Block Technology - Minhat, Mohamad; Xu, Xun (2009)
There has been much interest in ISO 14649 as a data model for CNCs. This project examines a CNC vertical milling machine operated by an ISO 14649 data model and utilizing the IEC 61499 technology. Instead of coding the tool path for a CNC machine directly, ISO14649 just provides the information required in the machining tasks. Therefore, to make a STEP-NC machine, tool path must be generated. A STEP-NC controller is developed based on a personal computer and an adaptor. The system is developed using the proposed language and in the JAVA environment. The STEPNC file is arranged in the Function Block software editor, which implements the structure and format in a STEP-NC file and is used as an input file